The Influence of Workload on Employee Performance of PT Cemara Agung Perdana Sumedang - Mulyani, Tami Sri; Ginanjar, Yayat; Henriawan, Desan (Journal of Bussines Management Basic, 2025)
This study analyzes the effect of workload on employee performance on 36 employees at PT Cemara Agung Perdana Sumedang. The method used is descriptive quantitative with random sampling techniques, and data collection through interviews, questionnaires, and documentation. Data analysis includes validity, reliability, normality, simple regression, and hypothesis testing. The results showed that the total score of respondents' responses to workload was 1,257 which was in the good category, and the total employee performance score of 2,218 was in the good category. However, there is a negative relationship between workload and performance with a coefficient of -0.511. The hypothesis proposed is whether there is an influence between workload on employee performance. The hypothesis testresults show a significant negative effect with tcount -3.880 > ttable 1.701.